Four Prognosis-Associated lncRNAs Serve as Biomarkers in Ovarian Cancer - Zheng, Jianfeng; Guo, Jialu; Zhang, Huizhi; Cao, Benben; Xu, Guomin; Zhang, Zhifen; Tong, Jinyi (Frontiers in Genetics, 2021)
Long noncoding RNAs (lncRNAs) play crucial roles in ovarian cancer (OC) development. However, prognosis‐associated lncRNAs (PALs) for OC have not been completely elucidated. Our study aimed to identify the PAL signature of OC. A total of 663 differentially expressed lncRNAs were identified in the databases. According to the weighted gene co-expression analysis, the highly correlated genes were clustered into seven modules related to the clinical phenotype of OC. A total of 25 lncRNAs that were significantly related to overall survival were screened based on univariate Cox regression analysis. The prognostic risk model constructed contained seven PALs based on the parameter λmin , which could stratify OC patients into two risk groups. The results showed that the risk groups had different overall survival rates in both TCGA and two verified GEO databases. Univariate and multivariate Cox regression analyses confirmed that the risk model was an independent risk factor for OC. Gene enrichment analysis revealed the identified genes were involved in some pathways of malignancy. The ceRNA network included five PALs, of which four were selected for cell function assays. The four PALs were downregulated in 33 collected OC tissues and 3 OC cell lines relative to the control. They were shown to regulate the proliferative, migratory, and invasive potential of OC cells via CCK-8 and transwell assays. Our study fills the gaps of the four PALs in OC, which are worthy of further study.